Bureaucratic discretion and legislative oversight on the budget process in Mexico 2001-2012 - Velázquez-López Velarde, Rodrigo (Economía Sociedad y Territorio, 2015)
The article analyzes the extent to which democratization increased the level of legislative control over the budget process during the first twelve years of democracy in Mexico. Two components of legislative oversight are examined in detail: Hacienda’s financial information available to legislators and the legislation regulating the government’s capacity to allocate and reallocate federal funds. The article finds that while legislators have formal rights to control the bureaucracy, public officials have informal leverage over members of Congress, as well. By distributing resources that legislators can use for patronage purposes, bureaucrats obtain legislators’ consent to implement programs at their convenience.